2020
DOI: 10.32883/hcj.v5i2.780
|View full text |Cite
|
Sign up to set email alerts
|

Peran Lemak Epikardial Pada Penyakit Jantung Koroner Stabil

Abstract: <p><em>Visceral fat tissue widely known have endocrine function by secreting Cytokines that provide it function in metabolism of visceral organ such as heart. It function have pivotal role under physiology and patology condition by secreting antiinflamatory cytokines in physiology condition, otherwise  proinflammatory cytokines in patology condition. Epicardial fat tissue as regard this function, have more important role to the heart, because it have two advantage than other visceral depots. First,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…From Table 3, information is obtained that the area of visceral fat in women is greater than the area of visceral fat in men, which is 83.71 cm 2 with a total volume of visceral fat of 1739.8 cm 3 . Whereas in men, the visceral fat area is 70.82 cm 2 with a total volume of 1036.23 cm 3 . In 2002, a Japanese study on 1,193 patients found that the VFA (Visceral Fat Area) value of 100 cm 2 is a proper cut-off for predicting patients with more than one clinical diagnosis, such as dyslipidemia, hyperglycemia, and hypertension.…”
Section: Segmentation Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…From Table 3, information is obtained that the area of visceral fat in women is greater than the area of visceral fat in men, which is 83.71 cm 2 with a total volume of visceral fat of 1739.8 cm 3 . Whereas in men, the visceral fat area is 70.82 cm 2 with a total volume of 1036.23 cm 3 . In 2002, a Japanese study on 1,193 patients found that the VFA (Visceral Fat Area) value of 100 cm 2 is a proper cut-off for predicting patients with more than one clinical diagnosis, such as dyslipidemia, hyperglycemia, and hypertension.…”
Section: Segmentation Resultsmentioning
confidence: 96%
“…Subcutaneous fat will be distributed as much as 80-90% into the body. At the same time, visceral fat is stored in the abdominal cavity, associated with the digestive tract, as much as 10-20% [3]. Visceral fat tissue is one of the tissues that can secrete cytokines that play a role in the function and metabolism of the visceral organs, including the heart [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation